A eficiência do gasto público na educação superior: uma análise da execução orçamentária da UFPB no período de 2015 a 2018 - Nóbrega Neto, Luis Alves da (2020)
In the scope of Public Management, this study favors the evaluation of the efficiency of public spending in Higher Education, analyzing the budget execution of a Federal Institution of Higher Education (IFES) that promotes teaching, research and extension, more specifically the Federal University of Paraíba (UFPB). The research aims to evaluate the level of efficiency of public spending of UFPB, through the analysis of the budget execution for the period 2015 to 2018. As for the methodology, this is a case study, of a quantitative and descriptive nature, whose research environment is the UFPB. Regarding the objectives, the study is characterized as a documentary research, whose data collection took place in the Union Accounting System (SIAFI) and in the Teaching Centers themselves. The data were analyzed and interpreted by Data Envelorder Analysis (DEA), which aimed to evaluate the efficiency related to the remuneration of the employees and the coefficient of performance of students graduated in the undergraduate course of the study, in the face-to-face modality. At the institutional level, our analysis resulted in the possibility of a broad understanding of how the resource is invested in personnel and what the return would be to the entity. However, through the results achieved, it was possible to determine trends and indicators that can be used as aid tools for decision-making. Finally, concluding that there was a decrease in the capital resources available in most Teaching Centers, with an asymmetric distribution of resources among 16 units surveyed, not taking into account individual efficiency (fine product/graduate student), since the transfer of resources is due more to the specificities of the courses than to planning factors. Being able to infer that, although the scenario was economic crisis, UFPB was able, as far as possible, to successfully execute capital expenditures, following the equipment (constant and necessary) that public heritage needs, to offer a decent, free and quality education